Analisis Faktor-faktor Penyebab tidak Optimalnya Penggunaan Laboratorium IPA di Sekolah Menengah Atas: - Susana Susana; Chensqy Dwi Cahyani; Ira Nopita Sari (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
Laboratory analysis is not optimal because the equipment used is outdated and has not been calibrated routinely, so the test results are less accurate. This study aims to analyze the factors that cause the suboptimal use of science laboratories in Senior High Schools (SMA). Science laboratories have an important role in science learning to improve students' conceptual understanding and practical skills. However, many schools have not utilized this facility optimally. The study used a descriptive approach with a survey method, involving science teachers and laboratory heads as respondents. The results of the analysis showed several main factors, namely the lack of budget for equipment maintenance and procurement, minimal laboratory staff competence, lack of time allocated in the curriculum, and low teacher motivation in designing practical activities. In addition, the limited number of tools and materials for practical work is also a significant obstacle. Recommendations from this study include increasing laboratory staff training, adequate budget allocation, and better integration between laboratory activities and classroom learning. Optimizing science laboratories is expected to support improving the quality of science education. This study recommends increasing the allocation of education budgets, continuous teacher training, and better laboratory management planning to improve the utilization of science laboratories. With these steps, laboratories can function optimally as learning facilities that support the development of students' science skills.